DIVERSITY OF BUTTERFLIES (LEPIDOPTERA) IN MOUNT BROMO FOREST AREA WITH SPECIAL PURPOSE (FASP), KARANGANYAR, CENTRAL JAWA - Rizqi Adanti Putri Pertiwi; Sugiyarto Sugiyarto; Agung Budiharjo; Ike Nurjuita Nayasilana (ZOO INDONESIA, 2020)
Butterflies are insects that must be preserved because of their role in balancing ecosystems. The purpose of this study is to know the diversity of butterflies in Mount Bromo FSAP. This research was conducted in May-August 2019. The observation site consisted of four stations, i.e. heterogeneous forest, cultivation field, sonokeling forest, and pine forest. Observation in each station was replicated three times. Time research was applied by making a 200m x 100m plot area in each station. Abiotic factors including humidity, temperature, light intensity, and wind speed were also measured in each station. Several ecological indices of butterflies were determined, including Shannon-Wiener Diversity Index (H'), Evenness Index (E), and Dominance Index (C). They were analyzed descriptively and associated with the nectar plants and abiotic factors. The result showed there are 42 species butterflies belong to five families in Mount Bromo FSAP. The butterfly diversity index is 2.78 or medium category with details 2.38, 2.50, 2.52, and 2.23 for the heterogeneous forest, cultivation field, pine forest, and sonokeling forest respectively. The diversity of butterflies is determined by the number of nectar plant, and abiotic factors suitable for butterfly activity.